(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
MANETs are ad Hoc networks characterized by dynamic topologies over time, open wireless medium, infrastructure less to control communications... etc. These networks are susceptible to various denial of service attacks such as black holes, which are considered among the most dangerous and serious threats. In order to mitigate black hole attacks, several intrusion detection systems have been proposed, like sequence number-based systems and trust-based systems, unfortunately these systems has become inefficient against the new wave of black holes, known also by smart black holes. Indeed, for example smart black holes can defeat threshold-based systems, by predicting the fixed threshold of the sequence number and can defeat the trust-based systems by checking if the RREQ is valid or not. In this paper, we have studied the impact of smart black holes on sequence number based systems and trust-based systems. We simulated, in NS2.35, several ad hoc networks with different densities under different number of smart black holes. Through simulation, it has been found that the smart black holes can easily defeat most of the proposed IDS in the literature